2006
DOI: 10.1002/jcla.20146
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of BNP and NT-proBNP assays in the approach to the emergency diagnosis of acute dyspnea

Abstract: N-terminal pro-brain natriuretic peptide (NT-proBNP) and BNP measurement could have a significant role in differentiating dyspnea between cardiac or pulmonary origin in the emergency room. The development of new and different commercial assays for these B-type natriuretic peptides offers the possibility of improving and simplifying their measurements but this could be defaulted due to the differences in methodology and the lack of assay standardization. We compared four available methods of measuring NT-proBNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 23 publications
1
9
0
2
Order By: Relevance
“…Although both BNP and N-terminal proBNP measurements generally correlate well with each other and both have been used successfully for perioperative risk stratification, the absolute values of BNP and N-terminal proBNP are not interchangeable. 31,32 Furthermore, there is a variability in absolute values of measurements made with various commercially available BNP assays. 33 Thus, although results of this study, particularly with regard to cut-points in peak postoperative BNP, should be considered specific to the BNP assay used in this study, future studies should focus on risk stratification cutoffs for different BNP and N-terminal proBNP assays in both primary CABG and other cardiac surgical cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Although both BNP and N-terminal proBNP measurements generally correlate well with each other and both have been used successfully for perioperative risk stratification, the absolute values of BNP and N-terminal proBNP are not interchangeable. 31,32 Furthermore, there is a variability in absolute values of measurements made with various commercially available BNP assays. 33 Thus, although results of this study, particularly with regard to cut-points in peak postoperative BNP, should be considered specific to the BNP assay used in this study, future studies should focus on risk stratification cutoffs for different BNP and N-terminal proBNP assays in both primary CABG and other cardiac surgical cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…All of the used assays showed acceptable analytic performance [11,13,30,31]. Further studies, however, are needed to confirm that the identical cut-off points can be used with the novel assays as validated with the Biosite assay or Roche NTproBNP assay.…”
Section: Laboratory Assaysmentioning
confidence: 97%
“…Measurement of NTproBNP/BNP in the emergency department improved the evaluation and treatment of patients with acute dyspnea and reduced the time to discharge and the total cost of treatment [5,7,[92][93][94]. Several studies have reported that NTproBNP and BNP present similar diagnostic accuracies for the differential diagnosis of dyspnea [9][10][11][95][96][97]. Lainchbury et al [1] suggested that differences in sensitivity and specificity may influence the assay choice in this setting.…”
Section: Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…BNP is derived from the precursor peptide proBNP, which is cleaved into the inactive amino-terminal fragment (NT-proBNP) comprising the first 76 amino acids of proBNP and the biologically active BNP hormone (BNP 1-32) (2). BNP is constantly elevated in states of increased ventricular wall stress and the measurement of circulating BNP and N-terminal proBNP (NT-proBNP) help to identify and guide the therapy of patients with both acute and chronic heart failure (HF) (3,4) and might also have a significant role in differentiating origin of dyspnea either cardiac or pulmonary in the emergency room (5). Additionally, in patients with chronic HF and acute and chronic coronary syndrome, both elevated BNP and NTpro-BNP are markers of unfavorable prognosis, being associated with increased mortality (6).…”
Section: Introductionmentioning
confidence: 99%